T-wave alternans in long QT syndrome - Siddharth Narayan Gadage (Annals of Pediatric Cardiology, 2018)
Long QT syndrome (LQTS) is a congenital disorder characterized by prolongation of QT interval in the electrocardiogram (ECG) and a propensity to develop ventricular arrhythmias, which may lead to syncope, cardiac arrest or sudden death. T-wave alternans (TWA), a phenomenon of beat-to-beat variability in the repolarization phase of the ventricles, has been closely associated with an increased risk of ventricular tachyarrhythmic events (VTE) and sudden cardiac death (SCD).